Correction: Microfluidic devices powered by integrated elasto-magnetic pumps. Issue 15 (24th June 2021) - Binsley, Jacob L.; Martin, Elizabeth L.; Myers, Thomas O.; Pagliara, Stefano; Ogrin, Feodor Y.
Abstract : Correction for 'Microfluidic devices powered by integrated elasto-magnetic pumps' by Jacob L. Binsley et al., Lab Chip, 2020, 20, 4285–4295, DOI: ; 10.1039/D0LC00935K .